Economic and biological evaluation of Сhinese cabbage [Brassica rapa L. var. pekinensis (Lour.) Kitam.] hybrids grown in the Right-Bank Forest Steppe of Ukraine - З. І. Ковтунюк; В. І. Войтовська; Л. І. Сторожик (Plant Varieties Studying and Protection)
Purpose. To study the economic and biological characteristics and to reveal the genetic potential of various hybrids of Chinese cabbage depending on the climatic zone of cultivation. Methods. In the experiment, hybrids of Chinese cabbage ‘Pioner F1’ (control), ‘Villi F1’, ‘Manoko F1’, ‘Orient Star F1’, ‘Vitimo F1’, ‘Sprinkin F1’, ‘Summer Highland F1’, ‘Suprin F1’, and ‘Richi F1’ were evaluated. The experiment was laid out in a randomized block design with four replications with a single plot area of 21 m2. The container seedlings (40 days old) were planted in the middle of April according to the scheme 70 cm by 25 cm. Results. Having been planted at the same time, seed germination over the studied hybrids was not simultaneous. The first sprouted seeds (4 days after seeding) belonged to hybrids ‘Villi F1’, ‘Manoko F1’, ‘Orient Star F1’, and‘Summer Highland F1’. Seeds of the other hybrids started active germination on the 5–6 days after seeding. The highest yield of the cabbage heads was obtained from hybrids ‘Villi F1’ (31.7 t/ha) and ‘Sprinkin F1’ (28.7 t/ha), which was 10.0 and 7.0 t/ha more than in the control variant. The yield of ‘Summer Highland F1’ was 24.9 t/ha and ‘Suprin F1’ 24.6 t/ha. Under the conditions of unstable soil moisture, hybrids ‘Villi F1’and ‘Sprinkin F1’ appeared the most productive and ensured yield increase of 10.0 t/ha and 7.0 t/ha, respectively, compared to the control; and crop commercial quality was high. The highest percentage of dry matter (DM) content was in ‘Summer Highland F1’ (6.2%) followed by ‘Sprinkin F1’ (5.9%), which was 1.1% and 0.8% more than in the control. There was no significant difference between the values of the total sugars content over the variants. They ranged between 1.7 and 2.1%, which was similar to the control values. The content of nitrates in the cabbage heads of the studied Chinese cabbage hybrids was within the tolerance limit and amounted to 600 mg/kg (raw mass). Conclusions. Phenological observations of plant development and their biometric indices, depending on the varietal characteristics, indicate that under the conditions of unstable soil moisture, hybrids ‘Villi F1’ and ‘Sprinkin F1’ were more yielding and ensured yield increase of 10.0 t/ha and 7.0 t/ha, respectively, compared to the control. The crop commercial quality was high. The long growing season of ‘Richi F1’ (93 days) did not affect the crop quality and yield and demonstrated the lowest productivity compared to the control and the other experiment variants.